Load-Aware Spectrum Distribution in Wireless LANs - Moscibroda, Thomas; Chandra, Ranveer; Wu, Yunnan; Sengupta, Sudipta; Bahl, Victor; Yuan, Yuan (ICNP 2008: 16th IEEE International Conference on Network Protocols, Orlando, Florida, 2008)
Traditionally, the channelization structure in IEEE 802.11-based Wireless LANs has been fixed: Each access point (AP) is assigned one channel and all channels are equally wide. In contrast, it has recently been shown that even on commodity hardware, the channel-width can be adapted dynamically purely in software. Leveraging this capability, we study the use of dynamic-width channels, where every AP adaptively adjusts not only its center-frequency, but also its channel-width to match its traffic load. This gives raise to a novel optimization problem that differs from previously studied channel assignment problems. We propose efficient spectrum-distribution algorithms and evaluate their effectiveness through analysis and simulations using realworld traces. Our results indicate that by allocating more spectrum to highly-loaded APs, the overall spectrum-utilization can be substantially improved and the notorious load-balancing problem in WLANs can be solved naturally.